2007
DOI: 10.1097/qai.0b013e318042e1ee
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Neuropsychologic Deficits Despite Long-Term Highly Active Antiretroviral Therapy in Patients With HIV-Related Neurocognitive Impairment

Abstract: The severity of NCI at HAART initiation seems to be the strongest predictor of persistent NP deficits despite long-term HAART. Our data indicate that HAART should be initiated as soon as NCI is diagnosed to avoid potentially irreversible neurologic damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
212
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(226 citation statements)
references
References 25 publications
12
212
0
2
Order By: Relevance
“…Furthermore, the current CD4 count at diagnosis had no impact on the performance of the NCD test we used. This finding has been reported in Botswana [15] and corroborates the facts reported that the CD4 count as well as other biomarkers such as plasma viral load and the cerebrospinal fluid are not correlated or are not predictive of neurocognitive disorders [46]. The finding that the current CD4 count is not associated with the performance on IHDS was predictable since most subjects received HAART.…”
Section: The Cd4 Count At Treatment Initiationsupporting
confidence: 80%
“…Furthermore, the current CD4 count at diagnosis had no impact on the performance of the NCD test we used. This finding has been reported in Botswana [15] and corroborates the facts reported that the CD4 count as well as other biomarkers such as plasma viral load and the cerebrospinal fluid are not correlated or are not predictive of neurocognitive disorders [46]. The finding that the current CD4 count is not associated with the performance on IHDS was predictable since most subjects received HAART.…”
Section: The Cd4 Count At Treatment Initiationsupporting
confidence: 80%
“…9,10 With the advent of highly-active antiretroviral therapy (HAART) in the mid-to-late ’90s, 11 the neurocognitive sequelae of HIV have lessened in severity 1214 and become somewhat more variable in expression, 15 although mild neurocognitive deficits persist. 13,1619 Although the current cognitive impairment-profile of HIV is relatively mild for many individuals, it is nonetheless predictive of significant decline in daily functioning. 20 Also, significant variability in HAART adherence patterns among HIV+ individuals 21 may account for recent reports of variable neurocognitive expression of HIV.…”
mentioning
confidence: 99%
“…23 Whereas a study from Canada noted 80% male patients. 24 In our study, also males dominate the sample (60.9%) males. People in certain profession have been found to be more susceptible to contract HIV.…”
Section: Discussionmentioning
confidence: 89%